Iowa fall bird report contributed by Babs Padelford and Loren Padelford, fall 1987 - Padelford, Babset al; Padelford, Lorenet al (1987)
Fall report of birds and locations contributed by Babs Padelford and Loren Padelford. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1987. Epson - sheet feed